Penerapan Media Bola Voli Berbahan Ban Bekas untuk Meningkatkan Aktivitas dan Hasil Belajar - R Dimas Dwi Suryananda; Rizki Apriliyanto; Bachtiar Hari Hardovi (Universitas Hamzanwadi, 2026)
Limited instructional equipment and low student engagement remain important barriers to effective volleyball instruction in physical education. This study examined changes in students’ learning activity, learning outcomes, and mastery status following the implementation of reused-tire learning media integrated with pedagogical improvements. A quantitative classroom action research design was conducted in two cycles involving 36 eleventh-grade students at SMA Negeri 01 Kalisat. Learning activity was assessed using a structured observation sheet comprising 10 indicators, while learning outcomes were measured through a 10-item multiple-choice test. Data were analyzed using descriptive statistics, the Shapiro–Wilk test, paired-samples t-tests, Cohen’s effect sizes, and the McNemar test with IBM SPSS Statistics version 27. The mean learning activity score increased from 27.56 to 36.50, , , with a very large effect size (). The mean learning outcome score increased from 74.28 to 84.11, , , with a large effect size (). The proportion of students achieving mastery increased from 50.00% to 91.67%, with a significant change according to the McNemar test (). These findings indicate that reused-tire learning media, when integrated with clearer demonstrations, structured group management, repeated practice, motivation, and immediate feedback, can support more active, contextual, and affordable volleyball instruction.